Digitalization Processes in Supply Chain Management as a Factor of Forming Smart Cities and the Improvement of the Quality of Urban Environment - Rachitovna Safina, Guzel; Essuman-Quainoo, Benedict; Alekseevna Fedorova, Viktoria (International Journal of Supply Chain Management, 2019)
The concentration of population in large cities causes the emergence of problems leading to a decrease in the quality of the urban environment. Currently, one of the key urban trends of modern times is represented by smart cities (“smart-city”). The development of the digital environment, which is reflected in the functioning of various spheres of citizens' life, contributes to the formation of a high-quality urban environment in modern conditions. The aim of this work is to examine the digitalization processes in Russian and foreign practice, which act as prerequisites for the creation of smart cities in the context of improving the quality of the urban environment. The authors use such theoretical research methods as analysis, synthesis and scientific synthesis. The concept of “smart city” (“smart-city”) involves reducing the environmental burden, efficient use of resources, the introduction of digital technologies, the creation of a comfortable and healthy living environment. This concept is implemented in a number of developed countries in Asia, Europe and America. Russia is also exploring and attempting to implement the concept of